HUBUNGAN PENGETAHUAN DAN KEPATUHAN DIET RENDAH GARAM TERHADAP HIPERTENSI PADA LANSIA DI WILAYAH KERJA PUSKESMAS REJOSARI KOTA PEKANBARU - Carles Carles; Emi Yulita; M. Irwan M. Irwan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
ABSTRACTElderly suffering from hypertension in an effort to reduce blood pressure by reducing salt intake, lack of knowledge and disobedience of the elderly will affect the failure of pressure reduction therapy in the elderly. Data was collected using a questionnaire sheet and a sphygmonometer. The sample was determined by simple random sampling method as many as 84 respondents in the Rejosari Health Center Pekanbaru City. This study used a descriptive correlative design with a cross-sectional design. The analysis was carried out by univariate analysis and bivariate analysis using the chi-square test. This research was conducted on July 15-5August 2022. Based on the results of the chi-square test, the results showed that there were 20 respondents (23.8%) who had a good level of knowledge and 35 respondents (41.7%) who had a sufficient level of knowledge, while 29 respondents (34.5%) have a low level of knowledge. Statistical test results obtained p-value 0.001 (p-value <0.005), it can be said that there is a relationship between knowledge of low salt diet and hypertension in the working area of Rejosari Health Center Pekanbaru. And based on the chi-square test, the results showed that there were 34 respondents (40.5%) who complied and 50 respondents (59.5%) who did not. Statistical test results obtained p-value 0.004 <0.005 (p-value <0.005), so it can be said that there is a relationship between low-salt diet adherence to hypertension in the elderly in the Rejosari Public Health Center Pekanbaru. It is expected that the elderly with hypertension will change their lifestyle by increasing knowledge of hypertension, by reducing the intake of high-salt foods or low-salt diets.